“Mother Earth:” From Myth to Science and its Entry into Catholic Social Thought - Agosta, Eduardo (Razón y fe, 2025)
The concept of “Mother Earth” has evolved from its mythical and cultural roots to become a contemporary symbol of the ecological crisis and planetary interdependence. Through an analysis of its archaeological and religious origins, the article examines how various traditions, including Christianity, have reinterpreted the maternal figure of the Earth. Its foundations in the Bible are explored, where the land that groans and cries out in the Hebrew prophets and St. Paul reveals a deep interconnection between humanity and creation. Finally, Pope Francis’ social thought, especially in Laudato si’, re-signifies this ecological responsibility and creaturely fraternity metaphor. Thus, the notion of “Mother Earth” reflects an ethical and prophetic call to care for the planet and is articulated with the science of the Earth system and planetary boundaries as a framework for environmental justice.